2021
DOI: 10.3892/ol.2021.12748
|View full text |Cite
|
Sign up to set email alerts
|

Predictive effects of preoperative serum CA125 and AFP levels on post‑hepatectomy survival in patients with hepatitis B‑related hepatocellular carcinoma

Abstract: The association between the serum levels of cancer antigen 125 (CA125; also termed MUC16) and the prognosis of patients with hepatocellular carcinoma (HCC) has not been widely reported to date. The aim of the present study was to determine the association between preoperative serum CA125 levels and prognosis of patients with hepatitis B virus (HBV)-related HCC after hepatectomy. The study included 306 patients with HBV-related HCC who underwent liver resection and were classified into four subgroups based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“… 19 Consistent with previous studies, our results suggest that CA125 is an adverse prognostic factor for EC. However, the specificity of CA125 as a tumor marker of EC is not high because the serum CA125 level will increase to varying degrees when non-EC patients suffer from endometriosis, 6 hepatitis 7 and tuberculosis, 20 when pregnant, or when in the inflammatory response period. Therefore, in the present study, we combined RDW-CV with CA125 for prognosis analysis, and the results showed that compared with CA125 or RDW-CV alone, RDW-CV+CA125 had a better prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Consistent with previous studies, our results suggest that CA125 is an adverse prognostic factor for EC. However, the specificity of CA125 as a tumor marker of EC is not high because the serum CA125 level will increase to varying degrees when non-EC patients suffer from endometriosis, 6 hepatitis 7 and tuberculosis, 20 when pregnant, or when in the inflammatory response period. Therefore, in the present study, we combined RDW-CV with CA125 for prognosis analysis, and the results showed that compared with CA125 or RDW-CV alone, RDW-CV+CA125 had a better prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…At present, cancer antigen 125 (CA125), is associated with the prognosis of EC. 5 However, when patients with non-EC suffer from endometriosis, 6 hepatitis, 7 or when the body is in the inflammatory response period, the level of serum CA125 will also increase to varying degrees. Therefore, the specificity of CA125 as a tumor marker for EC is not high, and it is not recommended to use CA125 alone as a prognostic indicator of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there was a higher mutation rate occurred in MUC16 gene in the IRGPI highrisk group than IRGPI low-risk group (18 vs. 11%). It has been reported that high baseline MUC16 level is associated with poor prognosis in patients with HBV-related HCC (Qin et al, 2021). The two exemplar genes indicated that IRGPI high-risk patients bearing high TP53 and MUC16 mutations often have worse outcomes than IRGPI low-risk patients bearing low TP53 and MUC16 mutations, which is in agreement with the results of survival analysis.…”
Section: Discussionsupporting
confidence: 86%
“… 10 Many studies have shown that CA125 can predict LNM in EC. 11 However, the level of serum CA125 can increase to varying degrees, such as in endometriosis 12 and hepatitis, 13 which indicates that the specificity of CA125 as a tumor marker for EC is not high. Therefore, it is of great significance to actively seek scientific and effective LNM prediction methods for the formulation of treatment plans for patients with EC.…”
Section: Introductionmentioning
confidence: 99%